(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
This study aims to research the diuretic properties of ethanolic extract of whole plant of Setaria glauca by Lipschitz model in albino rats. Ethanolic extract of S. glauca was administered to experimental albino rats orally at 2000 mg/kg p.o. The acute toxicity of the extract was evaluated as per OECD guideline 420–425. The LD50 of the extract was found to be between 2000 mg/kg p.o. male albino rats (n=6) were divided up into four groups. the control group was given saline as usual albino rats were divided into four groups to assess the diuretic activity of ethanolic extract of whole plant of S. glauca metabolic cages are used. group II contains furosemide (10 mg/Kg, p.o.) while groups III and IV receive saline as the control group’s vehicle. (100 mg/kg), medium (200 mg/kg), dosing of ethanolic extract of whole plant of S. glauca, respectively. Immediately following the methanolic extract of S. glauca, treatment Three rats were placed in each metabolic cage and kept at 21°C ± 0.5°C while all the rats were hydrated with saline (10 mL/kg, p.o.). urine the volume was measured. Each hour until the conclusion of the 5th hour and of each creature was calculated. The diuretic action and diuretic activity were decided based on the urine yield. Moreover, concentration of urinary sodium, chloride, and potassium particles was decided. The urinary Na+/K+ proportion and carbonyl anhydrase movement (Cl-/(Na+/K+)) where moreover surveyed. Animals were denied access to nutrient and water for a period of 5 hours. At the conclusion of the 5 hours, the total amount of urine accumulated with each metabolic cage has been measured. The volume of urine as well as the levels of the different ions, such as sodium, potassium, and chloride, were evaluated. Rats’ urine volume and concentration of urinary electrolytes increase because of the aqueous crude extract and of S. glauca.